Iron oxides impact sulfate-driven anaerobic oxidation of methane in diffusion-dominated marine sediments - Yorshansky, Omer; Liang, Lewen; Pellerin, André; Wang, Fengping; Herut, Barak; Sivan, Orit (Frontiers in Marine Science, 2022)
Microbial iron (Fe) reduction by naturally abundant iron minerals has been observed in many anoxic aquatic sediments in the sulfidic and methanic zones, deeper than it is expected based on its energetic yield. However, the potential consequence of this “deep” iron reduction on microbial elemental cycles is still unclear in sediments where diffusion is the dominant transport process. In this contribution, we experimentally quantify the impact of iron oxides on sulfate-driven anaerobic oxidation of methane (S-AOM) within the sulfate methane transition zone (SMTZ) of marine diffusive controlled sediments. Sediments were collected from the oligotrophic Southeastern (SE) Mediterranean continental shelf and were incubated with 13C-labeled methane. We followed the conversion of 13C-labeled methane as a proxy of S-AOM and monitored the sediment response to hematite addition. Our study shows microbial hematite reduction as a significant process in the SMTZ, which appears to be co-occurring with S-AOM. Based on combined evidence from sulfur and carbon isotopes and functional gene analysis, the reduction of hematite seems to slow down S-AOM. This contrasts with methane seep environments, where iron oxides appear to stimulate S-AOM and hence attenuate the release of the greenhouse gas methane from the sediments. In the deep methanic zone, the addition of iron oxides inhibits the methanogenesis process and hence methane gas production. The inhibition effect deeper in the sediment is not related to Fe-AOM as a competing process on the methane substrate, since Fe-AOM was not observed throughout the methanic sediments with several iron oxides additions.